Data Concentrator - Dvorský, Petr (Vysoké učení technické v Brně, Fakulta elektrotechniky a komunikačních technologií, 2021)
The topic of this paper is the design and realization of a modular Data concentrator forvarious types of measurements in diverse conditions. The device conception and basic principlesare described herein. Also, the lightweight protocol design for radio communication is described.The electrical design of the device as well as the design of the printed circuit board was made usingthe Eagle Autodesk electronic design automation software (Eagle Autodesk EDA). Control softwarefor a target microcontroller (ESP32-WROOM-32) is based on a FreeRTOS platform andESP-IDF framework. An IDE for managing this software is Visual Studio Code with PlatformIOextension.
Keywords: data concentrator; eagle autodesk; visual studio code; platformio; cloud